Atomic structural visualization on γ-Ho2Si2O7 using iDPC-STEM technique and its correlation with thermal expansion as advanced environmental barrier coating. (January 2023) - Lv, Xirui; Luo, Yixiu; Cui, Jingping; Zhang, Jie; Zhang, Lei; Wang, Jingyang
Abstract: γ-Ho2 Si2 O7 has attracted considerable attention as advanced environmental barrier coating (EBC) material for SiCf /SiC CMC due to its matchable thermal expansion coefficient (CTE) with Si-based ceramics. Negative phonons anharmonicity driven by crystal structure are thought to play a significant role in its thermal expansion behavior. In this work, atomic vibrations of γ-Ho2 Si2 O7 are investigated by ab-initio molecular dynamics simulation, Raman, and infrared spectra. The results confirm that transverse vibration of bridge O atoms in rigid [Si2 O7 ] units with linear configuration assure negative contribution to thermal expansion during thermal cycling. Moreover, atomic visualization is achieved by integrated differential phase contrast (iDPC)-STEM technique, and both heavy (Ho) and light (Si, O) atoms in γ-Ho2 Si2 O7 are clearly discerned. The acquired images provide a direct understanding to the origin of above mechanisms by capturing projection of all atomic columns along [100]. This work provides new insights into investigation of RE silicates through structural visualization and will facilitate the material design for advanced EBCs. Highlights: Transverse vibration of bridge O atoms in [Si2 O7 ] units assure low thermal expansion. Linear [Si2 O7 ] units are confirmed by combined Raman and FTIR spectra. Linear [Si2 O7 ] units and relatively free bridge O atoms are visualized by iDPC STEM.